Rheotechnological Approach to Increasing the Efficiency of Technological Processes in Oil Production - Mammadova , Y.V. (Herald of Azerbaijan Engineering Academy, 2021)
The article discusses the tasks of identifying the features of the lifting process of abnormal oils that significantly affect the flow rate of the working agent, and the appointment of uniform modes for wells with similar geological and technical operating conditions. The analysis of the results showed that the reason for the formation of an increased volume of the gas phase in the borehole fluid, in comparison with the formation oil. When lifting viscoelastic oils, unlike viscous oils, such phenomena as slippage of the injected gas are excluded, which brings its work closer to the process of piston displacement. When assessing the relaxation time of non-Newtonian oils, it was found that with an increase in temperature, a degeneration of viscoelastic properties is noted, which in turn affects, under the same conditions, the specific consumption of the working composition, which tends to increase.